Prebiotics: A Novel Approach to Treat Hepatocellular Carcinoma. (10th May 2017) - Fatima, Naz; Akhtar, Tasleem; Sheikh, Nadeem
Abstract : Hepatocellular carcinoma is one of the fatal malignancies and is considered as the third leading cause of death. Mutations, genetic modifications, dietary aflatoxins, or impairments in the regulation of oncogenic pathways may bring about liver cancer. An effective barrier against hepatotoxins is offered by gut-liver axis as a change in gut permeability and expanded translocation of lipopolysaccharides triggers the activation of Toll-like receptors which stimulate the process of hepatocarcinogenesis. Prebiotics, nondigestible oligosaccharides, have a pivotal role to play when it comes to inducing an antitumor effect. A healthy gut flora balance is imperative to downregulation of inflammatory cytokines and reducing lipopolysaccharides induced endotoxemia, thus inducing the antitumor effect.